Improving Underhand Serve Skills in Volleyball Through the Boy-Boyan Game Approach for Fifth-Grade Students - Muh. Adnan Hudain; Muhammad Arif HR; Sudirman Sudirman (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Elementary students frequently encounter difficulties with the underhand serve in volleyball, perceiving the technique as both challenging and monotonous, resulting in diminished engagement and inadequate skill acquisition. This study evaluates the effectiveness of the traditional Boy-boyan game to improve underhand serve skills among fifth graders at Elementary School 189 Inpres Cambajawa, Maros Regency. Using a Classroom Action Research (CAR) design over two cycles—comprising planning, action, observation, and reflection, the study involved 22 students selected through total sampling. Data were collected via performance tests, observation sheets, and documentation, then analyzed using quantitative descriptive methods. The results indicated a substantial, progressive enhancement in student performance. In the pre-cycle, the average score was 63.64 with a completion rate of only 14% (3 students). Following the intervention of Cycle I, the average rose to 71.31 (45% completion), which remained below the success threshold. In Cycle II, the average score increased dramatically to 86.65, with the completion rate reaching 95% (21 students), effectively surpassing the 80% classical success indicator. The findings indicate that the Boy-boyan game improves skills by aligning the mechanics of the traditional throwing motion with the underhand serve technique. Furthermore, the gamified approach created an enjoyable learning environment that reduced psychological barriers, boosting student confidence and motivation. This study concludes that integrating local traditional games into the modern sports curriculum is a highly effective strategy for enhancing motor skills and engagement in physical education.